What Went Wrong with the Veil? A Comparative Analysis of the Discourse of the Veil in France, Iran, and Indonesia - Safitri, Dian Maya (Al-Jamiah: Journal of Islamic Studies, 2010)
This paper attempts to discuss several current issues about the veil. ThreeÂ  countries are selected, namely France, Iran, and Indonesia, due to their different policies and perspectives concerning the veil. Using discourse analysis, this paper examines the violation of human rights, particularly those of Muslim women, by the ban of the veil in France and the obligation to wear it in Iran. Finally, inspired by the theoretical work of Gramsci, this paper analyzes how theÂ  terms âsecularâ and âreligiousâ are used by the state to justify their hegemony over certain minority groups. Moreover, this paper offers the âcorrect concept ofÂ  secularismâ as that entails civic reason, constitutionalism, and human-rights based citizenship, and proposed by An-Naâim as the best avenue to safeguard the problem of human rights in France and Iran. The remainder of this paper discusses Indonesia, the largest Moslem country in the world, that is, in fact, âa secular countryâ based on Pancasila, which respects religious freedom, includingÂ  for women to wear the veil or not. It also opens full, equal, and fair access for all Indonesian women, regardless of their ethnicity and religious affiliation,Â  to compete in the workforce and to pursue education. The authorâs intention is to clarify false stereotypes about the veil, to enlighten readers about abuse of power by both French and Iranian governments in violating the rights of women on the issue of veil, and to inform readers --using the case of IndonesiaÂ  as an example-- about the importance of state neutrality in supporting the rights of freedom of and from religion.